Implementation of Standard Operating Procedures, Quality of Work Environment, and Employee Performance: A Quantitative Approach - Slamet Heri Winarno; Lela Elvira; Mahmud Syarif; Mety Titin Herawaty (MultiTech Publisher, 2024)
This study investigates the impact of the implementation of Standard Operating Procedures (SOPs) and the influence of the workplace's quality on workers performance using a quantitative approach. In today's competitive business landscape, optimizing employee performance is crucial, and this research aims to identify key factors contributing to performance enhancement. A structured survey was administered to employees across various sectors, and the data were analysed using statistical methods to determine the relationships between the variables. The findings reveal a significant positive correlation between the rigorous implementation of SOPs and improved worker productivity. Furthermore, the standard of the workplace was found to play a critical role in moderating this relationship, suggesting that a supportive and well-maintained work environment enhances the effectiveness of SOPs. The study provides empirical evidence that both SOPs and work environment quality are integral to boosting employee performance. These results underscore the importance of well-defined procedures and a conducive work environment in organizational strategies aimed at improving workforce productivity. Recommendations for managers include ensuring consistent application of SOPs and investing in creating a positive work environment to foster better performance outcomes.